Caffeine influences performance, muscle pain, muscle damage marker, but not leukocytosis in soccer players - Pereira, L. N.; Machado, M.; Antunes, W. D.; Tamy, A. L. M.; Barbosa, A. A. L.; Pereira, R. (Medicina Sportiva, 2012)
Caffeine is commonly used by athletes to improve exercise performance but the effects of caffeine supplementation on strenuous intermittent exercise performance, perceived muscle pain, muscle damage markers and immunological response in soccer players are not conclusive. Objective: To evaluate the effect of caffeine supplementation on strenuous intermittent exercise performance, perceived muscle pain, muscle damage markers and immunological response in soccer players. Methods: Twenty male professional soccer players completed a placebo-controlled double blind test protocol. At 45 min before exercise, participants ingested 5.5 mg·kg-1 body mass of caffeine (CAF, n=10) or cellulose (PLA, n=10). The exercise was 2 trials of 6 sets of 10 sprints (20m each) with 10s recovery time between sprints, 2 min between sets and 15 min between trials followed by a strenuous intermittent exercise (Yo-Yo intermittent recovery test; Yo-Yo IRT). The performance of Yo-Yo IRT, the perceived muscle pain before exercise protocol, after sprints and after Yo-Yo IRT were recorded. Blood samples were collected before, immediately, 24 and 48h after exercise for serum creatine kinase (CK) activity quantification and immunological cell count. Results: Caffeine improved the performance during the strenuous intermittent exercise and reduced the perceived muscle pain along the exercise protocol (sprints and Yo-Yo IRT), without influence on muscle damage markers and immunological response. Conclusions: Our results suggest that caffeine (5.5 mg·kg-1 BM) produce large reduction in pain resulting from strenuous intermittent exercise which is associated to the performance gains of soccer players. Additionally, the used caffeine dosage has no influence upon serum CK activity, reflective of muscle integrity and damage, and upon immunological cell count.